Endogamous Marriage as a Criteria for Kafaah in the Arab Community of Jember Based on Al-'Adah Muhakkamah Perspective - Naimah Alasdaq; Deni Irawan (Indonesian Journal of Law and Islamic Law (IJLIL), 2023)
The purpose of this study is to ascertain and comprehend the perspectives of Ulama about kafaah in endogamous marriage, as well as the practises and perspectives of al-'Adah Muhakkamah in endogamous marriage within the Arab community of Jember. The research methodology employed in this study is field research, utilising a juridical, normative, and sociological approach. The findings of this study indicate that some Ulama perceive endogamous marriage as a component of moderate compatibility (kafaah), while others do not. Furthermore, the majority of the Arab community in Jember agrees with the viewpoint of Ulama who believe that endogamous marriage is not a part of kafaah. After analysis, it was concluded that the implementation of endogamous marriage was acceptable because it was in accordance with the principles of al-'Adah Muhakkamah.